Hubungan Gaya Kepemimpinan Kepala Ruangan Intensif Terhadap Budaya Keselamatan Pasien Rumah Sakit Umum Unimedika Setu Bekasi Tahun 2024 - Tyas, Aulia Rahma Ning; Pangkey, Dicky Yulius; Ambarini, Tinon (Jurnal Manajemen dan Administrasi Rumah Sakit Indonesia (MARSI), 2025)
Background: Based on Law Number 17 of 2023, concerning hospitals, it states that a hospital establishment must have very complete health service facilities. This study analyzes the relationship between the leadership style of the head of the intensive care unit and the culture of patient safety at Uni Medika Setu Hospital, Bekasi, considering that the data results prefer a transactional leadership style reaching 44% in 2023. Method: Mixed Method Research, with a combination of Quantitative and Qualitative, involving a sample of 70 Nurses. Data were analyzed using Chi Square. Results: Leadership styles with the Transactional, Transformational, and Mixed types have no statistical differences, but when conducted through interviews, the Transactional style is more dominant. Conclusion: Any type of leadership style has the same results in terms of statistical tests, but it is different if the interview results are different, nurses prefer the Transactional leadership style. Keywords: Leadership Style, Nurses, Patient Safety Culture